Examples with solutions for Parentheses in simple Order of Operations: Solving the problem

Exercise #1

(159)×(73)= (15-9)\times(7-3)=

Video Solution

Step-by-Step Solution

According to the order of operations rules, we must first solve the expressions inside of the parentheses:

159=6 15-9=6

73=4 7-3=4

We obtain the following expression:

6×4=24 6\times4=24

Answer

24 24

Exercise #2

Solve the following expression:

(85+5):10= (85+5):10=

Video Solution

Step-by-Step Solution

Let's simplify this expression while following the order of operations which states that exponents come before multiplication and division, which come before addition and subtraction, and that parentheses come before all of them,

We will therefore start by simplifying the expression inside the parentheses and calculate the result of the addition within them, then - we will first perform the division operation:

(85+5):10=90:10=9 (85+5):10= \\ 90:10= \\ 9

Therefore, the correct answer is answer A.

Answer

9 9

Exercise #3

187×(85)= 187\times(8-5)=

Video Solution

Step-by-Step Solution

We'll use the distributive property and multiply each term in parentheses by 187:

187×8187×5= 187\times8-187\times5=

Let's solve the first multiplication problem vertically, making sure to solve it correctly, meaning units times units, units times tens, units times hundreds.

187×8 187\\\times8

We get the result: 1496

Let's solve the second multiplication problem vertically, making sure to solve it correctly, meaning units times units, units times tens, units times hundreds.

187×5 187\\\times5

We get the result: 935

Now we'll get the problem:

1496935= 1496-935=

We'll solve this vertically as well. We'll make sure to align the digits properly, units under units, tens under tens, etc.:

1496935 1496\\-935

We'll subtract units from units, tens from tens, etc., and get the result: 561 561

Answer

561 561

Exercise #4

(30+6):4×3= (30+6):4\times3=

Video Solution

Step-by-Step Solution

According to the order of operations, first we solve the exercise within parentheses:

30+6=36 30+6=36

Now we solve the exercise

36:4×3= 36:4\times3=

Since the exercise only involves multiplication and division operations, we solve from left to right:

36:4=9 36:4=9

9×3=27 9\times3=27

Answer

27

Exercise #5

Solve the following problem using the order of operations:

(166)×9+(73)= (16-6)\times9+(7-3)=

Video Solution

Step-by-Step Solution

According to the order of operations, we'll first solve the exercises in parentheses:

(166)=10 (16-6)=10

(73)=4 (7-3)=4

We should obtain the following exercise:

10×9+4 10\times9+4

We'll place the multiplication exercise in parentheses to avoid confusion in the rest of the solution:

(10×9)+4= (10\times9)+4=

According to the order of operations, we'll solve the multiplication exercise and then add:

90+4=94 90+4=94

Answer

94 94

Exercise #6

(126+9)×(7+3)= (12-6+9)\times(7+3)= ?

Video Solution

Step-by-Step Solution

According to the order of operations, we will first solve the expressions in parentheses and then multiply:

(126+9)=(6+9)=15 (12-6+9)=(6+9)=15

(7+3)=10 (7+3)=10

Then solve the multiplication exercise:

15×10=150 15\times10=150

Answer

150 150

Exercise #7

(8:4:2)31= (8:4:2)-3-1=

Video Solution

Step-by-Step Solution

According to the rules of the order of operations, we first solve the exercise within parentheses from left to right:

8:4=2 8:4=2

2:2=1 2:2=1

Now we get the exercise:

131= 1-3-1=

We solve the exercise from left to right:

13=2 1-3=-2

21=3 -2-1=-3

Answer

3-

Exercise #8

Solve the exercise:

2×3(4+5):2= 2\times3-(4+5):2=

Video Solution

Step-by-Step Solution

According to the rules of the order of operations, we first solve the exercise within parentheses:

4+5=9 4+5=9

Now we obtain the exercise:

2×39:2= 2\times3-9:2=

We place in parentheses the multiplication and division exercises:

(2×3)(9:2)= (2\times3)-(9:2)=

We solve the exercises within parentheses:

2×3=6 2\times3=6

9:2=4.5 9:2=4.5

Now we obtain the exercise:

64.5=1.5 6-4.5=1.5

Answer

1.5 1.5

Exercise #9

Solve the following:

4+(6+6:3)2= 4+(6+6:3)\cdot2=

Video Solution

Step-by-Step Solution

Let's simplify this expression while adhering to the order of operations which states that exponents come before multiplication and division, which come before addition and subtraction, and that parentheses take priority over all.

In our expression, there is a term in parentheses that needs to be multiplied. We'll start by simplifying this expression, remembering that division comes before addition, so we'll first perform the division operation within the parentheses and then the addition operation in this expression:

4+(6+6:3)2=4+(6+2)2=4+82= 4+(6+6:3)\cdot2= \\ 4+(6+2)\cdot2= \\ 4+8\cdot2=

Let's continue simplifying the expression we that we got in the last step. Since multiplication comes before addition, we'll first calculate the multiplication in the expression and then perform the addition operation:

4+82=4+16=20 4+8\cdot2= \\ 4+16= \\ 20

To summarise:

4+(6+6:3)2=4+82=20 4+(6+6:3)\cdot2= \\ 4+8\cdot2= \\ 20

Therefore the correct answer is answer C.

Answer

20

Exercise #10

Solve the following expression:

10(104):2= 10-(10-4):2=

Video Solution

Step-by-Step Solution

Let's simplify this expression while following the order of operations which states that exponents come before multiplication and division, which come before addition and subtraction, and that parentheses come before all of them,

Therefore we'll start by simplifying the expression inside the parentheses and perform the subtraction within them, then since division comes before subtraction, we'll first perform the division operation and then the subtraction operation

10(104):2=106:2=103=7 10-(10-4):2= \\ 10-6:2= \\ 10-3=\\ 7 Therefore the correct answer is answer D.

Answer

7 7

Exercise #11

10(104):2= 10-(10-4):2=

Video Solution

Step-by-Step Solution

Let's simplify this expression while following the order of operations which states that exponents come before multiplication and division, which come before addition and subtraction, and that parentheses come before all of them,

We will start by simplifying the expression inside the parentheses and calculate the result of the subtraction within them, then - since division comes before subtraction, we will first perform the division operation and then perform the subtraction operation:

10(104):2=106:2=103=7 10-(10-4):2= \\ 10-6:2= \\ 10-3= \\ 7

Therefore, the correct answer is answer B.

Answer

7

Exercise #12

(13×2)(12×1.5)= (13\times2)-(12\times1.5)=

Video Solution

Step-by-Step Solution

According to the order of operations, we will first solve the multiplication exercises in parentheses:

(13×2)=26 (13\times2)=26

(12×1.5)=18 (12\times1.5)=18

Now we will subtract:

2618=8 26-18=8

Answer

8 8

Exercise #13

6(3+5213)= 6\cdot(3+5\cdot2-13)=

Video Solution

Step-by-Step Solution

Let's simplify this expression while following the order of operations which states that exponents come before multiplication and division, which come before addition and subtraction, and that parentheses come before all of them,

Therefore, we'll start by simplifying the expression in parentheses, since multiplication comes before addition and subtraction we'll first perform the multiplication in the expression and then calculate the result of the addition and subtraction operations in the expression:

6(3+5213)=6(3+1013)=60=0 6\cdot(3+5\cdot2-13)= \\ 6\cdot(3+10-13)= \\ 6\cdot0= \\ 0 We completed the calculation above by performing the remaining multiplication, and we also remembered that multiplying any number by 0 will always result in 0.

Therefore, the correct answer is answer B.

Answer

0

Exercise #14

4+(6+6:3)2= 4+(6+6:3)\cdot2=

Video Solution

Step-by-Step Solution

Let's simplify this expression while following the order of operations which states that exponents come before multiplication and division, which come before addition and subtraction, and that parentheses come before all of these,

Therefore, we'll start by simplifying the expression in parentheses, and since division comes before addition, we'll first perform the division operation in this expression and then the addition operation:

4+(6+6:3)2=4+(6+2)2=4+82 4+(6+6:3)\cdot2= \\ 4+(6+2)\cdot2= \\ 4+8\cdot2 \\ We'll continue to simplify the expression we got in the last step, remembering that multiplication comes before addition and therefore we'll first perform the multiplication in the expression and then the addition operation:

4+82=4+16=20 4+8\cdot2= \\ 4+16= \\ 20 Therefore, the correct answer is answer C.

Answer

20 20

Exercise #15

17(3542+23)= 17-(3\cdot5-4\cdot2+2\cdot3)=

Video Solution

Step-by-Step Solution

Let's simplify this expression while following the order of operations which states that exponents come before multiplication and division, which come before addition and subtraction, and that parentheses come before all of them,

Therefore, let's start by simplifying the expression inside the parentheses, remembering that multiplication comes before addition and subtraction and thus we will first perform the multiplications in this expression, then perform the subtraction operations, and finally complete the calculation by performing the subtraction operation on the expression in parentheses:

17(3542+23)=17(158+6)=1713=4 17-(3\cdot5-4\cdot2+2\cdot3)= \\ 17-(15-8+6)= \\ 17-13= \\ 4

Therefore the correct answer is answer C

Answer

4